PENGEMBANGAN BAHAN AJAR KONSEP PECAHAN BERBANTUAN MULTIMEDIA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DI SEKOLAH INKLUSI - Sudihartinih, Eyus; Amaliah, Ikhlasul Amaliah (Jurnal Pendidikan (Teori dan Praktik), 2019)
The purpose of this study was to find out the form of teaching materials for fractional calculating operations on multimedia assisted of mathematics learning to improve students' mathematical understanding skills in inclusive schools. Mathematical understanding is all forms of thought processes taken in forming the structure of knowledge. Indicators of mathematical understanding used in this study are students can distinguish the material that has been studied with the previous material, students can formulate how the material has been learned, students can deduce what material has been learned, and students can solve mathematical problems in everyday life relating to the material he has learned. Students in inclusive schools are more diverse than the common school so that teachers need to brainwave how to make classroom learning more interesting. Multimedia learning can be the solution to these problems.